UNIT 29.11 General qPCR and Plate Reader Methods for Rapid Optimization of Membrane Protein Purification and Crystallization Using Thermostability Assays. (1st August 2014) - Tomasiak, Thomas M.; Pedersen, Bjørn P.; Chaudhary, Sarika; Rodriguez, Andrew; Colmanares, Yaneth Robles; Roe‐Zurz, Zygy; Thamminana, Sobha; Tessema, Meseret; Stroud, Robert M.
Abstract: This unit describes rapid and generally applicable methods to identify conditions that stabilize membrane proteins using temperature‐based denaturation measurements as a proxy for target time‐dependent stability. Recent developments with thiol‐reactive dyes sensitive to the unmasking of cysteine residues upon protein unfolding have allowed for routine application of thermostability assays to systematically evaluate the stability of membrane protein preparations after various purification procedures. Test conditions can include different lipid cocktails, lipid‐detergent micelles, pH, salts, osmolytes, and potential active‐site ligands. Identification and use of conditions that stabilize the structure have proven successful in enabling the structure determination of numerous families of membrane proteins that otherwise were intractable. Curr. Protoc. Protein Sci . 77:29.11.1‐29.11.14 © 2014 by John Wiley & Sons, Inc.